PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA 2007-2011 - Anthomi Wibisono Limanto (Business Accounting Review, 2014)
This study aimed to know the influence of Good Corporate Governance implementation on firm value listed in Indonesian Stock in the period 2007-2011. The measurement of the GCG was measured by using proxy of GCG Score. GCG Score it self is measured through Rights of Shareholders, The Board of Commissioners, Independent Commissioner, Audit Committee, Internal Audit and Disclosure to Investors. Control variables used are Age, Market Share, and Industrial Sectors. The samples used was 40 companies.This research was done in all industrial sectors listed in Indonesian Stock Exchange and have complete data in accordance with this research. This result proved that Corporate Governance Index and Market Shares didn’t exceed more than 0.05. It stated that these two variables had significant positive influence toward the firm’s value. Age influenced significantly but had negative relation towards the firm’s value. And there were industrial sectors that had influence (D3,D4,D5,D7,D8 and D9) and some that didn’t have influence (D1 and D2) towards the firm’s value